Analisis Hubungan Teori Health Belief Model dengan Kepatuhan Pengobatan Penderita Diabetes Mellitus Tipe 2 di Wilayah Kerja Puskesmas Galala - Haswini Harun; Hary Chandra (Inovasi Kesehatan Global, 2025)
Non-communicable diseases (NCDs) are the leading cause of death globally, with type 2 diabetes being one of the most prevalent conditions. Nutritional management for clients with type 2 diabetes requires strict adherence to the correct schedule, type, and quantity of food. To improve medication adherence, it is essential to implement preventive strategies that promote patient engagement and self-management. One such strategy is the Health Belief Model (HBM), which encourages patients to adopt healthy behaviors based on their perceptions of risk, severity, benefits, and barriers. This study aims to analyze the relationship between the Health Belief Model and medication adherence among type 2 diabetic patients in the Galala Community Health Center (Puskesmas) work area. A quantitative cross-sectional study design was used, with a sample size of 108 participants selected through simple random sampling. The independent variables in this study were perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action, while the dependent variable was medication adherence. The results revealed significant relationships between all the HBM constructs and medication adherence. Specifically, perceived susceptibility (p=0.000), perceived severity (p=0.000), perceived benefits (p=0.000), perceived barriers (p=0.000), and cues to action (p=0.000) all had strong associations with adherence to medication. The findings suggest that the Health Belief Model is a valuable framework for improving medication adherence among type 2 diabetes patients. Additionally, the use of health information technology is an effective strategy to increase patient awareness of the risks of non-adherence and the importance of regular medication intake. A combination of education, social support, technology, and an individualized approach can create a supportive environment that encourages patients to manage their treatment effectively.